2015
DOI: 10.3892/mmr.2015.4583
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin induces apoptosis in the U-2OS human osteosarcoma cell line via triggering the mitochondrial pathway

Abstract: Abstract. Bufalin has been shown to induce apoptosis in osteosarcoma cells; however, the underlying mechanism has not been elucidated. The purpose of the present study was to investigate whether mitochondria-mediated signaling pathways trigger the process of apoptosis in the U-2OS osteosarcoma cell line. Bufalin inhibited the proliferation and induced apoptosis in U-2OS cells in a time-and dose-dependent manner. Bufalin-induced apoptosis was accompanied with a significant reduction of the mitochondrial membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Bufalin inhibited cell growth via the down-regulation of Bcl-2/Bax and the triggering of the mitochondrial pathway in human osteosarcoma MG-63 cells [ 31 ]. Recently, it was reported that bufalin induced apoptosis in the U-2 OS human osteosarcoma cell line via triggering of the mitochondrial pathway [ 28 ]. However, the molecular mechanisms for the effects of bufalin on human osteosarcoma U-2 OS cells OS remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bufalin inhibited cell growth via the down-regulation of Bcl-2/Bax and the triggering of the mitochondrial pathway in human osteosarcoma MG-63 cells [ 31 ]. Recently, it was reported that bufalin induced apoptosis in the U-2 OS human osteosarcoma cell line via triggering of the mitochondrial pathway [ 28 ]. However, the molecular mechanisms for the effects of bufalin on human osteosarcoma U-2 OS cells OS remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in our laboratory, we found that bufalin induced DNA damage in NCI-H460 cells and also inhibited its DNA repair and checkpoint function [ 26 ]. Numerous studies have shown that bufalin induced cytotoxic effects through the induction of apoptosis in many human cancer cells including human osteosarcoma U-2 OS cells [ 27 , 28 , 29 ], human osteosarcoma MG-63 cells [ 30 ], and both MTX-sensitive and MTX-resistant human osteosarcoma U-2 OS cells [ 31 ]; however, the possible molecular mechanisms of bufalin induced cytotoxic cell death involving endoplasmic reticulum (ER) stress in human osteosarcoma is still unclear. The possible molecular mechanisms of bufalin induced cytotoxic cell death involving endoplasmic reticulum (ER) stress in human osteosarcoma is still unclear; thus, we investigate the anticancer potential of bufalin against human osteosarcoma U-2 OS cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The induction of programmed cell death (apoptosis) by cytostatic agents is a common mode of action in cancer treatment and in OS chemotherapy in particular [ 103 , 104 , 105 ] and mitochondria act as the major regulator of apoptosis [ 96 ]. Triggered by specific signaling cascades, apoptosis results in cellular degradation and cell death without liberation of degradation products and critical biomolecules, which may induce systemic processes of inflammation or immune response [ 106 ].…”
Section: Cap Effects On Os Cellsmentioning
confidence: 99%
“…Additionally, a homogeneous polysaccharide (TRP) was isolated and purified from Trametes robiniophila Murrill, which could induce apoptosis through the intrinsic mitochondrial pathway in human osteosarcoma (U-2 OS) cells [64]. Furthermore, bufalin induced apoptosis in the U2OS human osteosarcoma cell line, which was accompanied with a significant reduction in mitochondrial membrane potential, the release of mitochondrial cytochrome c into the cytosol, the activation of caspase-3, caspase-9 and poly (adenosine diphosphate ribose) polymerase, as well as the downregulation of B-cell lymphoma 2 (Bcl-2)/Bcl-2-associated X protein; suggesting that bufalin induced apoptosis by triggering the mitochondrial pathway [65]. Baicalein is a new drug, and baicalein-induced apoptosis in osteosarcoma cells was via a mitochondrial pathway that involved both caspase-dependent and -independent mechanisms.…”
Section: Programmed Cell Death In the Treatment Of Osteosarcomamentioning
confidence: 99%